Near atomic-scale comparison of passive film on a 17 wt% Cr-added 18 wt% Mn steel with those on typical austenitic stainless steels. (October 2021) - Kim, Eun Tae; Ishtiaq, Muhammad; Chan Han, Jong; Ko, Kwang Kyu; Bae, Hyo Ju; Sung, Hyokyung; Kim, Jung Gi; Seol, Jae Bok
Abstract: The passive films on typical stainless steels (SS) and on a newly developed high-Cr (17 wt%)-added 18 wt%-Mn steel (HCr-HMnS) were compared by Cs-corrected scanning transmission electron microscopy and atom probe tomography. Although the passive films of all samples having similar Cr contents had the same thickness, unprecedented hexagonal wurtzite MnO inside the passive film of HCr-HMnS specimen was susceptible to corrosion cracking; this was not observed in the SS samples. This MnO caused crack formation during potentiodynamic polarization test, suggesting that reducing the harmful MnO by adding Mo and Ni facilitates the development of high-Mn base SS materials . Furthermore, higher MoO2 composition of the passive films on 316 type austenitic SS than 304 type series might would result in primarily the improved pitting resistance. Graphical abstract: Image, graphical abstract